The “Arm’s Length” Principle in Lithuanian Cultural Policy - Rimkutė, Audronė (Respectus Philologicus, 2014)
This article analyzes Lithuanian cultural policy, particularly the implementation of the “arm’s length” principle. The first part of the article describes the concept of the principle, gives an overview of its history, and examines its main instrument of implementation—the council for culture. The article compares the activity of similar councils in various countries and describes their most important functions and features. The second part of the article deals with the formation of the “arm’s length” cultural policy model in Lithuania. This model was chosen as the direction for cultural policy reform in the Lithuanian Government’s 1991 program, and was also recommended by the experts during Lithuania’s participation in the Council of Europe program National Cultural Policy Reviews 1996–1998. The process of forming the model lasted until 2013. The article analyzes public discussions about Lithuanian cultural policy, Lithuanian government programs, the main political documents, as well as the stages of the formation process and the causes of its slow progress. The third part deals with the operational problems of two Lithuanian “arm’s length” institutions that were established prior to the Lithuanian Council for Culture. Public comments on these two institutions and their activity reports are analyzed and the main weaknesses of their activity are discerned.